MEDIATING ROLE OF ESG RATINGS IN THE RELATIONSHIP BETWEEN GREEN FINANCE AND FINANCIAL PERFORMANCE: EVIDENCE FROM G20 COUNTRIES - MALIK, HILAL AHMAD; MALIK, DR. IMRAN RIAZ (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
Since the inception of green finance, it has gained considerable attention in academic, social, governmental, and financial sectors. Green financing enables firms to be perceived as environmentally friendly, socially responsible, and well-governed, which leads towards better financial outcomes. The purpose of this study is to examine the mediating role of ESG ratings in the relationship between green finance and financial performance. For this purpose, the study uses a panel of 489 firms issuing green finance from G20 countries. Generalized Method of Moments (GMM) technique is used for data analysis. Findings reveal that both green finance and ESG ratings lead to better financial outcomes. However, the impact of green finance is mediated by ESG ratings. This study contributes towards the extension of knowledge and provides a framework for firms and policymakers to show concern for sustainability. These dynamics can help corporate decision-makers to take strategic decisions aligned with sustainability goals and financial success.